Nutrition and Food Supplies - Standing Joint Committee of Industrial Women's Organisations (London : The Labour Party)
1936-09 1936 1930s 33 pages : illustration NUTRITION AND FOOD SUPPLIES [photograph] Published by THE LABOUR PARTY Transport House, Smith Square, London, S.W.1 2D. 127/NU/5/5/1/12